Efficacy of a vaccine and a direct-fed microbial against fecal shedding of Escherichia coli O157:H7 in a randomized pen-level field trial of commercial feedlot cattle - Cull, Charley A.; Paddock, Zachary D.; Nagaraja, T. G.; Bello, Nora M.; Babcock, Abram H.; Renter, David G. (My University, 2012)
Our primary objective was to determine the efficacy of a siderophore receptor and porin proteins-based vaccine (VAC) and a Lactobacillus acidophilus-based direct-fed microbial (DFM) against fecal shedding of Escherichia coli O157:H7 in commercial feedlot cattle fed a corn grain-based diet with 25% distiller's grains. Cattle projected to be on a finishing diet during the summer were randomly allocated into 40 study pens within ten blocks based on allocation dates. Blocks were complete; each of the four pens within a block was randomly assigned one treatment: control, VAC, DFM, or VAC+DFM. The DFM was fed (106CFU/animal/day of Lactobacillus) throughout the study periods (84–88 days) and cattle were vaccinated at enrollment and again three weeks later. Fresh fecal samples (30/pen) from pen floors were collected weekly for four consecutive weeks (study days 52–77). Two concurrent culture procedures were used to enable estimates of E. coli O157:H7 shedding prevalence and prevalence of high shedders. From 4800 total samples, 1522 (31.7%) were positive for E. coli O157:H7 and 169 (3.5%) were considered high shedders. Pen-level linear mixed models were used for data analyses. There were no significant interactions among treatments and time of sampling. However, vaccinated pens had lower (P<0.01) overall prevalence of E. coli O157:H7 (model-adjusted mean ±SEM=17.4±3.95%) and lower (P<0.01) prevalence of high shedders (0.95±0.26%) than unvaccinated pens (37.0±6.32% and 4.19±0.81%, respectively). There was no evidence of a DFM effect on either measure of E. coli O157:H7 shedding. Results indicate that a two-dose regimen of the vaccine significantly reduces fecal prevalence of E. coli O157:H7 (vaccine efficacy of 53.0%) and prevalence of E. coli O157:H7 high shedders (vaccine efficacy of 77.3%) in commercial feedlot cattle reared in the summer on a finishing diet with 25% distiller's grains.
Keywords: Cattle; Feedlot; Food safety; O157:H7; SRP; Vaccine